An extension of `green port portfolio analysis' to inland ports: an analysis of a range of eight inland ports in Western Europe - Michael Dooms; Elvira Haezendonck (European Regional Science Association (ERSA), 2004)
Haezendonck (2001) introduced an ecological dimension in conventional port portfolio analysis for seaports and applied it to the seaports in the Hamburg – Le Havre range. Given the fast growth of inland waterway transport, and the development of inland ports in the hinterland of seaports, the analysis can also be extended to evaluate the `green' competitiveness of inland ports, as they are considered as important enablers to reach objectives of sustainable development. In this paper, the `green port portfolio analysis' is applied to a range of eight inland ports in Western Europe. This results in (1) a number of specific methodological issues related to the inland port environment, (2) an interesting research agenda both for policy-makers at the local and regional level as well as for inland port managers. Keywords: Strategic management, port management & development
Keywords: 330; Strategic management; port management & development